EFEK PEMBERIAN EKSTRAK ETANOL BIJI PALA (Myristica fragrans Houtt) TERHADAP ANSIETAS MENCIT (Mus musculus) - Irin N. Hasanusi; Paringotan Y. Silalahi; Johan B. Bension; Laura B.S. Huwae; Ony W. Angkejaya; Yuniasih M. J. Taihuttu (Fakultas Kedokteran Universitas Pattimura, 2020)
Anxiety is excessive worry without reason related to certain precipitating factors. The content of the compound myristicin and alkaloids contained in the nutmeg plant (Myristica fragrans Houtt) can be as antianxiety, so that its use can prevent the dependence effect of most antianxiety drugs. This study aims to determine the effect of nutmeg ethanol extract on anxiety on mice (Mus muculus). This research is a true experimental with post test only control group design. The research subjects were 30 mice which were taken by simple random technique and divided into the normal control groups (KN), negative controls (K-), positive controls (K+), ethanol extract of nutmeg seeds at a concentration of 4% (P1), and ethanol extract of nutmeg seeds at a concentration of 16% (P2). In the group K-, K +, P1, and P2 were given stress treatment with the FST method for 6 minutes. Then in the K+ group were given a dose of alprazolam is 0.2 ml, P1 were given ethanol extract of nutmeg seeds at a concentration of 4% and P2 were given ethanol extract of nutmeg seeds at a concentration of 16%. The treatment is carried out for 7 days and on the 8th day will be tested with EPM. Observation data were analyzed using the ANOVA test. The results showed that the administration of ethanol extract of nutmeg seeds had a significant effect on the length of time the mice were in the open arms of EPM (p<0,05). The decrease of anxiety levels in the P1 and P2 mice in this study was due to the content of the myristicin, flavonoid and saponin compounds found in ethanol extract of nutmeg seeds.